2015
DOI: 10.1007/s10956-015-9567-3
|View full text |Cite
|
Sign up to set email alerts
|

Employing Augmented-Reality-Embedded Instruction to Disperse the Imparities of Individual Differences in Earth Science Learning

Abstract: Studies have proven that merging hands-on and online learning can result in an enhanced experience in learning science. In contrast to traditional online learning, multiple in-classroom activities may be involved in an augmented-reality (AR)-embedded e-learning process and thus could reduce the effects of individual differences. Using a three-stage AR-embedded instructional process, we conducted an experiment to investigate the influences of individual differences on learning earth science phenomena of ''day, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 33 publications
(33 reference statements)
0
40
0
5
Order By: Relevance
“…Although there is an acknowledgement that AR applications lead positive learning outcomes (Chen, & Wang, 2015;Radu, 2012), there was only three studies (11,19,22) focusing on the development of students' higher order thinking skills. However, the lack of or insufficient scientific evidence regarding the potential use of AR applications in supporting students' higher order thinking skills does not imply that researchers and educators should stop experimenting with those applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is an acknowledgement that AR applications lead positive learning outcomes (Chen, & Wang, 2015;Radu, 2012), there was only three studies (11,19,22) focusing on the development of students' higher order thinking skills. However, the lack of or insufficient scientific evidence regarding the potential use of AR applications in supporting students' higher order thinking skills does not imply that researchers and educators should stop experimenting with those applications.…”
Section: Discussionmentioning
confidence: 99%
“…The value (Chen, & Wang, 2015) and importance (Lee, 2012) of using AR applications in formal education is studied with respect to various learning outcomes. For instance, researchers investigated whether AR enhanced multimedia learning improves the retention of the delivered content, and found that students using AR multimedia contents improved knowledge retention as opposed to those following a traditional course (Pérez-López, & Contero, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is stated in these studies that the augmented reality provides important advantages in science education. However, studies have generally focused on the effect of augmented reality on cognitive factors (Bressler & Bodzin, 2013;Chen & Wang, 2015;Enyedy et al, 2012;Lin et al, 2013;Matcha & Rambli, 2013;Squire & Jan, 2007;Wang et al, 2014). The cognitive factors as well as affective factors (motivation, attitude etc.)…”
Section: Extended Abstractmentioning
confidence: 99%
“…Similarly, in an academic setting "simulations, online learning environments, and modelling software" and other means gain popularity (Janssen & Lazonder, 2015, p. 910). Undoubtedly, the use of devices and online learning provides the new possibilities (Chen & Wang, 2015). In particular, the students can comprehend scientific material better due to the excessive use of advanced visuals (LaDue, Libarkin, & Thomas, 2015).…”
Section: Importance Of the Problemmentioning
confidence: 99%